Corruption, public debt, political years, and economic growth in democratic developing countries - Rida Srihadiastuti; Mahjus Ekananda (Komisi Pemberantasan Korupsi, 2024)
This study investigates the impacts of political corruption and public debt on the economic progress of 43 democratic developing countries that have experienced varying election cycle frequencies from 2002 to 2021. The research utilizes a PMG-ARDL method and relies on data from the World Bank and International Monetary Fund (IMF). The results show that although corruption can generate ‘temporary’ benefits, it ultimately hinders long-term economic development. Our analysis also compares the impact by grouping countries based on different frequencies of election years, referred to as ‘political years’. In the group of countries with a ‘high’ frequency of political years, the impact of corruption is more detrimental than in the group of countries with a ‘low’ frequency. To anticipate the negative effects of corruption and ensure that the allocation of development funds is on target, we recommend: 1) improving the governance system to minimize corruption; 2) measuring corruption with new, more concrete indicators, not just the perception index; 3) implementing changes to the tax payment mechanism, as direct public control over budget allocations are often inefficient and leaky; and 4) improving the effectiveness of the campaign mechanism to prevent corruption by electoral candidates.